Heterologous Expression and Biochemical Characterization of the Human Zinc Transporter 1 (ZnT1) and Its Soluble C-Terminal Domain - Cotrim, Camila A.; Jarrott, Russell J.; Whitten, Andrew E.; Choudhury, Hassanul G.; Drew, David; Martin, Jennifer L. (Frontiers in Chemistry, 2021)
Human zinc transporter 1 (hZnT1) belongs to the cation diffusion facilitator (CDF) family. It plays a major role in transporting zinc (Zn2+) from the cytoplasm across the plasma membrane and into the extracellular space thereby protecting cells from Zn2+ toxicity. Through homology with other CDF family members, ZnT1 is predicted to contain a transmembrane region and a soluble C-terminal domain though little is known about its biochemistry. Here, we demonstrate that human ZnT1 and a variant can be produced by heterologous expression in Saccharomyces cerevisiae cells and purified in the presence of detergent and cholesteryl hemisuccinate. We show that the purified hZnT1 variant has Zn2+/H+ antiporter activity. Furthermore, we expressed, purified and characterized the soluble C-terminal domain of hZnT1 (hZnT1-CTD) in a bacterial expression system. We found that the hZnT1-CTD melting temperature increases at acidic pH, thus, we used an acetate buffer at pH 4.5 for purifications and concentration of the protein up to 12 mg/mL. Small-angle X-ray scattering analysis of hZnT1-CTD is consistent with the formation of a dimer in solution with a V-shaped core.